A Proposed Model for Reducing Energy Costs through Solar Energy in Agricultural Enterprises in Tunceli - Peker, Ayşe Esra (Munzur Üniversitesi, 2026)
Rising global energy demand and the environmental damage caused by the use of fossil fuels are accelerating the shift toward sustainable energy sources in the agricultural sector. In this context, solar energy systems [SES] emerge as a clean and cost-effective option for agricultural operations. In Türkiye, SES investments are concentrated in regions with long sunshine durations, particularly in Southeastern Anatolia, Central Anatolia, and the Mediterranean; specifically in Şanlıurfa, Gaziantep, and Mardin; Konya, Ankara, and Kayseri; and Antalya, Adana, and Mersin. While small-scale, industry-focused projects are common in the Aegean and Marmara regions, agricultural investments remain limited in the Black Sea and Eastern Anatolia regions. In Tunceli, the study area, SES applications for agricultural operations have not yet developed sufficiently. To this end, the Best-Worst Method [BWM] was integrated with Geographic Information Systems [GIS]. Sixteen criteria, categorized under topographic, socio-economic, technical, and spatial categories, were evaluated in line with the needs of the agricultural sector. According to the analysis, the areas surrounding Pertek and Mazgirt, as well as the southeastern part of the central district, have been identified as suitable locations for the installation of solar energy systems in agricultural enterprises.
Keywords: solar energy system; Geographic Information System; Best-Worst Method; Agricultural enterprises; Tunceli (Türkiye)